Ontologies for software engineering and software technology - Calero, Coral. (Springer Berlin Heidelberg, 2006)
Communication is one of the main activities in software projects, many such projects fail or encounter serious problems because the stakeholders involved have different understandings of the problem domain and/or they use different terminologies. Ontologies can help to mitigate these communication problems. Calero and her coeditors mainly cover two applications of ontologies in software engineering and software techonology: sharing knowledge of the problem domain and using a common terminology among all stakeholders; and filtering the knowledge when defining models and metamodels. The editors structured the contributions into three parts: first, a detailed introduction into the use of ontologies in software engineering and software technology in general; second, the use of ontologies to conceptualize different process-related domains such as software maintenance, software measurement, or SWEBOK, initiated by IEEE; third, the use of ontologies as artifacts in several software processes, like, for example, in OMG’s MOF or MDA. By presenting the advanced use of ontologies in software research and software projects, this book is of benefit to software engineering researchers in both academia and industry. Ontological engineering: principles, methods, tools and languages -- Using ontologies in software engineering and technology -- Engineering the ontology for the SWEBOK: issues and techniques -- An ontology for software development methodologies and endeavours -- Software maintenance ontology -- An ontology for software measurement -- An ontological approach to SQL: 2003 -- The object management group ontology definition metamodel -- Ontologies, meta-models, and the model-driven paradigm -- Use of ontologies in software development environments -- Semantic upgrade and publication of legacy data.